2011
DOI: 10.1080/13632461003668046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nonlinearity of Frame Buildings on Peak Horizontal Floor Acceleration

Abstract: Using representative numerical models of eight code-designed steel moment-resisting frame buildings and several ground motions, time-history analyses are performed and a critical evaluation of Peak Horizontal Floor Acceleration (PHFA) demands is conducted. The frames are modeled alternatively as linear and nonlinear systems to isolate the effect of building nonlinearity on PHFA. In most cases, PHFA is reduced when nonlinear behavior of a building is considered; however, in some cases, significant amplification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 13 publications
5
37
0
Order By: Relevance
“…It is worth noting that these periods were calculated assuming a linear time invariant system and that the mode shapes of the BI and FB building are completely different due to the influence of the building isolation system. These effects have been previously identified through numerical simulations (e.g., Rodriguez et al 2002, Ray Chaudhuri and Villaverde 2008, Ray Chaudhuri and Hutchinson 2011. It is noted that the variation between the PRA measured at the four corners during each motion was very small, with a coefficient of variation less than 5%.…”
Section: Building Responsesupporting
confidence: 54%
“…It is worth noting that these periods were calculated assuming a linear time invariant system and that the mode shapes of the BI and FB building are completely different due to the influence of the building isolation system. These effects have been previously identified through numerical simulations (e.g., Rodriguez et al 2002, Ray Chaudhuri and Villaverde 2008, Ray Chaudhuri and Hutchinson 2011. It is noted that the variation between the PRA measured at the four corners during each motion was very small, with a coefficient of variation less than 5%.…”
Section: Building Responsesupporting
confidence: 54%
“…Through the analysis of these three stripes, the variation of the PSDM properties with the nonlinearity level of the structural response is evaluated. Studies have shown, in fact, that FRS significantly change both in amplitude and shape when the structure gets into the nonlinear range (e.g., ).…”
Section: Illustrative Examplementioning
confidence: 99%
“…Among them are [18][19][20] and [21], which are limited to elastic primary structures, whereas in [9,22,23] and [24], methods have been developed, which are also applicable to inelastic structures. Among them are [18][19][20] and [21], which are limited to elastic primary structures, whereas in [9,22,23] and [24], methods have been developed, which are also applicable to inelastic structures.…”
Section: Introductionmentioning
confidence: 99%